Expressed emotions and perceived stress among patients and caregivers of patients suffering from bipolar affective disorder - Sharma, Renu; Ghai, Sandhya; Singh, Shubhmohan (International Journal of Scientific Reports, 2021)
Background: Expressed emotions (EE) are the critical, hostile and emotionally over- involved attitude of relatives towards a family member who is suffering from a disorder. It is a measure of the expressed attitude of the relatives towards their psychological patient in their absence. As, in bipolar affective disorder (BPAD) alternating/recurring periods of depression and elevated mood occurs which leads to varied levels of stress and expressed emotions in the patient as well as their caregivers. Methods: An exploratory study was conducted in psychiatry ward and psychiatry outpatient department (OPD) of PGIMER, Chandigarh on BPAD patients and their caregivers (N=50 each) using purposive sampling technique. Data was collected in the month of March for 10 days. Interviews were conducted using the modified perceived stress scale by Sheldon Cohen and Hooley’s expressed emotions scale for assessing expressed emotions levels, respectively. Results: Data analysis done with the help of statistical package for the social sciences (SPSS) 22 version 16.0 through descriptive and inferential statistics. The study revealed that 64% of caregivers face criticism from their patients whereas 62% of patients receive criticism from their caregivers. The study also showed that 68% of caregivers were given emotional support by their patients. 66% of caregivers and patients, both displayed moderate level of perceived stress. Conclusions: It can be concluded that both EE and perceived stress are significant stressors for the BPAD patients and their caregivers.